FLORIST'S MSME MARKETING STRATEGY IN INCREASING SALES AND BUSINESS COMPETITIVENESS - Suryani Lubis; Marina; Muhammad Ibrahim; Ariful Maulana; Amru Usman (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in driving economic growth and equitable distribution of income. However, many MSMEs still face challenges in implementing marketing strategies, particularly amidst technological advancements and increasingly digital consumer behavior. This study aims to analyze the marketing strategies implemented by the MSME YDP Florist to increase sales and business competitiveness. The research method used is a qualitative approach with data collection techniques through interviews, observations, and literature studies. The results show that YDP Florist has implemented offline and online marketing strategies utilizing digital media. The implementation of appropriate and integrated marketing strategies has been proven to have a positive impact on increasing sales and business competitiveness. This research is expected to serve as evaluation material and a reference for other MSMEs in developing effective marketing strategies.